Hidden Curriculum dalam Dimensi Pembangunan Karakter untuk Mengatasi Degradasi Moral Sekolah Dasar - Detu Maharani Puspita Sari; Wanda Tri Utami; Anang Jefry Nurfalaq; Koko Harguntoro (Universitas Indraprasta PGRI Jakarta, 2023)
The writing of this article aimed to explore the implementation of hidden curriculum in the dimensions of character development in elementary schools. This was done due to moral degradation in Indonesia and the importance of collaboration between teachers, principals, parents, and the community in the implementation of hidden curriculum in elementary schools. To achieve this goal, a literature review of hidden curriculum was presented based on five main themes highlighted in the literature: (a) definition of hidden curriculum, (b) function of hidden curriculum, (c) factors supporting the implementation of hidden curriculum, (d) moral degradation, and (e) implementation of hidden curriculum in the dimension of character development. The research method used a literature review which uses reference books and scientific articles. Analysis of hidden curriculum studies conducted in Indonesia in the character development dimension was presented by showing the impact of the implementation of hidden curriculum in all aspects. The writing of this article was expected to be able to contribute in the implementation of the dimensions of character development to overcome moral degradation in elementary schools. The impact of implementing the hidden curriculum useful in implementation of education Indonesia, especially in human rights, character development from the moral degradation of elementary school students.